The use of writ of habeas corpus under the Malaysian constitution / Nor Adibah Abd. Rahim - Abd. Rahim, Nor Adibah (Faculty of Law, 1986)
The aim of this Project Paper is to determine the general trend of the courts in Malaysia in issuing the writ of habeas corpus. This includes the study of the principles used by the courts in determining when a detained person is entitle to the writ of habeas corpus. This paper also . includes a study of approaches used by the courts in Malaysia compared to that used by courts in United Kingdom and India. This Project Paper is based on the Article 5(l)an^ 5(2) of the Federal Constitution for the discussion of substantive right and Criminal Procedure Code ( F.M.S. Chap. 6 ) for the procedural law in the issue of the writ of habeas corpus. The principles used by the courts in deciding on whether the writ of habeas corpus should be issued was based on decided cases. The law here is as it stands on 31 st. May 1986.